Research on Accurate Detection Algorithm for the Cross-Section of Shale Gas Casing Deformation Pipe String Based on Laser Ranging - Yang, Shangyu; Mou, Yisheng; Cao, Jing; Yan, Yan (Processes, 2024)
Under shear and non-uniform loads, the deformation of the section shape of a casing results in an irregular section, and the spatial continuity is poor. The change in the distance between the wall of the casing before and after stress is recorded to analyze the deformation of the casing, and the distance value is taken as the key characteristic of the casing. A large number of the key characteristic values of shale gas casing deformation can be obtained by using the circular traversal detection method. At the same time, this article focuses on the center deviation between the laser sensor axis and the pipe string axis, as well as on the disturbance problem during measurement. An eccentricity error correction algorithm is derived to correct the eccentricity error that occurs during the detection process, and then we use interpolation algorithms to draw cubic spline curves to improve detection accuracy. The test results show that the algorithm can effectively eliminate eccentricity errors in measurement and achieve the accurate measurement of deformation casing characteristic values, which can provide basic data for the study of a shale gas casing deformation mechanism.